2017
DOI: 10.18045/zbefri.2017.2.459
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Banking Sector Competition in the Cee Countries: The Panzar-Rosse Approach

Abstract: Competitive conditions in the banking sectors in the light of transition process in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Second explanatory variable, the ratio of interest expenses to total deposits (RIETD) is employed in the model to control the unit price of funds. In their research, [8], [11], [13], [14], and [16] also used the same proxy variable for control the unit price of funds. It is anticipated that this variable has a positive relationship with dependence variable because that more collected deposits increase loans portfolio and consecutively generates more revenues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second explanatory variable, the ratio of interest expenses to total deposits (RIETD) is employed in the model to control the unit price of funds. In their research, [8], [11], [13], [14], and [16] also used the same proxy variable for control the unit price of funds. It is anticipated that this variable has a positive relationship with dependence variable because that more collected deposits increase loans portfolio and consecutively generates more revenues.…”
Section: Methodsmentioning
confidence: 99%
“…The authors revealing that the banking sector acting under monopolistic competition. On the contrary, by using the GMM model [16], investigated the sample of 300 banks in CEE countries between 1999 and 2009. The findings of study indicate that banks in CEE countries exert monopoly behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to findings the Polish banking system has a monopolistic competitive market structure in the whole period, although the average H statistical value obtained as a result of three different models shows a fluctuating structure. Mustafa and Toçi (2017) examined the banking market competition conditions of 17 countries in Central and Eastern Europe (CEE) in the period 1999-2009. According to the H statistics value obtained from the dynamic panel data analysis using 300 bank data, it was found that CEE banks exhibit monopoly behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The nonstructural studies (e.g., Rodriguez, Bolivar, & Reyes, 2018;Demirel & Hatirli, 2017;Bikker, Shaffer, & Spierdijk, 2012;Aktan & Masood, 2010;Gischer & Stiele, 2008;Casu & Giradone, 2006) rely on Bresnahan-Lau model, Lener index, and the Panzar-Rosse model. Typically, studies of this nature identify the industry as monopolistically competitive, however, some characterize it as perfectly competitive (e.g., Shaffer, 1993;Nathan & Neave, 1989), oligopoly (e.g., Babic, Zildzovic, & Loncar, 2015;Mensi, 2010), or monopoly (e.g., Mustafa & Toci, 2017). The structural approach relies on proxies such as Herfindahl-Hirschman Index (HHI) and concentration ratio of n firms (CR n ) to elucidate the level of competition in the industry (Nguyen, 2019;Bikker, Shaffer, & Spierdijk, 2012;Berger, Demirguc-Kunt, Levine, & Haubrich, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%